Diagnosis of adult-onset MELAS syndrome in a 63-year-old patient with suspected recurrent strokes – a case report - Tim Sinnecker; Michaela Andelova; Michael Mayr; Stephan Rüegg; Michael Sinnreich; Juergen Hench; Stephan Frank; André Schaller; Christoph Stippich; Jens Wuerfel; Leo H. Bonati (BMC Neurology, 2019)
Abstract Background Mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS) is a mitochondrial cytopathy caused by mutations in mitochondrial DNA. Clinical manifestation is typically before the age of 40. Case presentation We present the case of a 63-year-old female in whom the symptoms of MELAS were initially misdiagnosed as episodes of recurrent ischemic strokes. Brain imaging including MRI, clinical and laboratory findings that lent cues to the diagnosis of MELAS are discussed. In addition, MRI findings in MELAS in comparison to imaging mimics of MELAS are presented. Conclusions This case underscores the importance of considering MELAS as a potential cause of recurrent stroke-like events if imaging findings are untypical for cerebral infarction, even among middle-aged patients with vascular risk factors.